(4x-1)(4x+1)(x-4)=0

Simple and best practice solution for (4x-1)(4x+1)(x-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (4x-1)(4x+1)(x-4)=0 equation:


Simplifying
(4x + -1)(4x + 1)(x + -4) = 0

Reorder the terms:
(-1 + 4x)(4x + 1)(x + -4) = 0

Reorder the terms:
(-1 + 4x)(1 + 4x)(x + -4) = 0

Reorder the terms:
(-1 + 4x)(1 + 4x)(-4 + x) = 0

Multiply (-1 + 4x) * (1 + 4x)
(-1(1 + 4x) + 4x * (1 + 4x))(-4 + x) = 0
((1 * -1 + 4x * -1) + 4x * (1 + 4x))(-4 + x) = 0
((-1 + -4x) + 4x * (1 + 4x))(-4 + x) = 0
(-1 + -4x + (1 * 4x + 4x * 4x))(-4 + x) = 0
(-1 + -4x + (4x + 16x2))(-4 + x) = 0

Combine like terms: -4x + 4x = 0
(-1 + 0 + 16x2)(-4 + x) = 0
(-1 + 16x2)(-4 + x) = 0

Multiply (-1 + 16x2) * (-4 + x)
(-1(-4 + x) + 16x2 * (-4 + x)) = 0
((-4 * -1 + x * -1) + 16x2 * (-4 + x)) = 0
((4 + -1x) + 16x2 * (-4 + x)) = 0
(4 + -1x + (-4 * 16x2 + x * 16x2)) = 0
(4 + -1x + (-64x2 + 16x3)) = 0
(4 + -1x + -64x2 + 16x3) = 0

Solving
4 + -1x + -64x2 + 16x3 = 0

Solving for variable 'x'.

The solution to this equation could not be determined.

See similar equations:

| 5y+2=22 | | 5-3(4-3*6)= | | 2-15m=5(-3n+2) | | 2z+4=8 | | (x+2)(x-2)(2x+5)=0 | | -11.5+.5p=.9p+5.1 | | 7*9-8+11-6[5+2(-3)]= | | .1(5x+20)-5=0.25(2x+8) | | 6x^3-22x^2+12x=0 | | (3r-1)(4r^2+2)= | | 31*2+25= | | (8x-3y)(8x+3y)=0 | | 10(12.7-1.25b)+6b=106.2 | | 3+(x*4)=9 | | 4*5+11= | | 11-7= | | x+23=2-2(x-8) | | (7a+b)(7a-b)=0 | | 3+8-7*5+11= | | 2x+4+x=14-2x | | 8a+10b=101.6 | | P(x)=6x^3-22x^2+12x | | (8a-2b)(8a+2b)=0 | | 2z+20=28 | | 14*6= | | 14*5= | | 8818*4= | | 2x-5y=15 | | (3x+5)(3x-5)=0 | | 8+2+4= | | y^2-4y+3= | | 8+2= |

Equations solver categories